Hubungan Riwayat Intervensi Gizi Spesifik Ibu Hamil dengan Stunting pada Balita di Puskesmas Banjarsari - Pertiwi Purwa Asri; Yuliawati Yuliawati; Rofana Aghniya; Yetti Anggraini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Stunting continues to be a significant public health concern due to its impact on children’s physical growth and cognitive development. Various prevention strategies have been implemented, particularly through specific nutritional interventions during pregnancy. Nevertheless, evidence regarding the effectiveness of different types of these interventions at the primary health care level is still limited. This study aimed to examine the relationship between maternal exposure to specific nutritional interventions during pregnancy and the occurrence of stunting among children under five at Banjarsari Primary Health Center, Metro City. A case-control study design was applied involving 66 pendddents (22 cases and 44 controls) selected from a population of 609 children using stratified random sampling. Data collection was carried out through interviews, observations, structured checklists, height measurements using a stadiometer, and review of maternal and child health (MCH) records. Statistical analysis was performed using the Chi-square test. The findings indicated that supplementary feeding (p=0.008; OR=7.8), iron and folic acid supplementation (p=0.007; OR=5.7), iodine-related education (p=0.010), and deworming education (p=0.042; OR=4.6) were significantly associated with stunting. In contrast, caffeine-related education (p=0.701), nutrition counseling (p=0.210), and calcium supplementation (p=0.188) showed no significant association. In summary, nutritional interventions with direct biological effects appear to have a stronger influence on stunting prevention. From a policy perspective, prioritizing high-impact interventions, enhancing adherence through integrated monitoring, and strengthening behavior change strategies are recommended to improve maternal nutrition services and reduce stunting rates.